Oil in the West African Transform Margin: Dangers and Possibilities. Issue 1 (2nd January 2016) - Obeng-Odoom, Franklin
ABSTRACT: The West African Transform Margin (WATM) is the new centre of oil exploration in Africa. Less is known about its experiences and more work is needed to unearth them. Viewed through the eyes of Frantz Fanon, Aimé Césaire, and Walter Rodney, the available evidence shows not only the persistence of grave limiting dangers about the colonial economic structure in this subregion but also major possibilities about inter- and intra-regional linkages. A strategy of alternative indigenous regional vision that de-emphasises economic growth and stresses autonomy, distribution, and energy sovereignty is shown to be workable, and superior to the status quo. How to make the transition will be challenging but the effort is worth making for by doing so the region will take control and direction of its resources, to plan, to develop, and to manage them, and hence to free itself from the debilitating shackles of the unjust economic order of the world system.